2017
DOI: 10.1098/rspa.2017.0354
|View full text |Cite
|
Sign up to set email alerts
|

Spectral derivation of the classic laws of wall-bounded turbulent flows

Abstract: We show that the classic laws of the mean-velocity profiles (MVPs) of wall-bounded turbulent flows—the ‘law of the wall,’ the ‘defect law’ and the ‘log law’—can be predicated on a sufficient condition with no manifest ties to the MVPs, namely that viscosity and finite turbulent domains have a depressive effect on the spectrum of turbulent energy. We also show that this sufficient condition is consistent with empirical data on the spectrum and may be deemed a general property of the energetics of wall turbulenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…The different curves correspond to different values of the dimensionless parameter β e . Note that the spectral model can reproduce all of the salient § Analysis of such generic aspects of the spectrum can be used to shed light on the scaling relations for the MVPs 2017). trends in the experimental and computational data (also shown in Figs.…”
Section: Equations Of the Mvpsmentioning
confidence: 99%
“…The different curves correspond to different values of the dimensionless parameter β e . Note that the spectral model can reproduce all of the salient § Analysis of such generic aspects of the spectrum can be used to shed light on the scaling relations for the MVPs 2017). trends in the experimental and computational data (also shown in Figs.…”
Section: Equations Of the Mvpsmentioning
confidence: 99%
“…Formulating RSL effects as an adjustment to C instead of U is desirable as dU=dz is Galilean invariant, whereas U is not. 29 On the practical side, extensions to stratified flow cases become convenient as / RSL can be framed as a generalized similarity function derived from the product of the standard form of the Monin-Obukhov 30 stability correction function and a function representing the RSL effects on C. Thus, / RSL ðÁÞ is a dimensionless roughness sublayer modification function yet to be determined and frames the scope of the work here for near-neutral stratification. Near-neutral stratification forms a logical starting point for any extension toward stratified cases in the future.…”
Section: Introductionmentioning
confidence: 99%
“…First experiments on turbulence in non-Newtonian fluids were already performed in 1959 [4]. Since then, most theoretical studies have focused on drag reduction [5,6], and the mathematical modeling of wall stresses and boundary layers [7][8][9]. For isotropic turbulence in dilute polymer solutions, De Angelis et al[10] found through DNS that relaxation connecting different scales significantly alters the energy cascade.Intuitively, in the inertial subrange, molecular stresses should have a negligible influence on the motion and size of the eddies, regardless of the rheological nature of the fluid [11].…”
mentioning
confidence: 99%
“…First experiments on turbulence in non-Newtonian fluids were already performed in 1959 [4]. Since then, most theoretical studies have focused on drag reduction [5,6], and the mathematical modeling of wall stresses and boundary layers [7][8][9]. For isotropic turbulence in dilute polymer solutions, De Angelis et al [10] found through DNS that relaxation connecting different scales significantly alters the energy cascade.…”
mentioning
confidence: 99%